Perspective on the Dependency of Using Grammarly in Thesis Writing: A Mixed Method Study - Nur Wahid Akhmad; Muhammad Basri Jafar; Samtidar (International Journal of Language, Education, and Literature, 2025)
The purpose of this research is to determine the perspective of students' dependence on using Grammarly as a technological tool to improve grammar in academic writing, in this case thesis. The influence of Grammarly on student writing, as well as finding out the level of dependence on students in using Grammarly. This research uses mixed methods, namely qualitative and quantitative research designs. The subjects of this research were nine university students who were participants in this research. This research used interviews and questionnaires to collect data. The results of the research show that in using Grammarly as technology or a tool to improve grammar in writing a thesis, researchers found that unhealthy use of Grammarly can result in dependence on students which can affect mental health and reduce students' independent writing skills. The dependency experienced by students can be excessive anxiety when writing without Grammarly. Researchers found that students were dependent on Grammarly with an accumulated score of 75.55% from the questionnaire distributed to students.